Oligocene Leucogranites of the Gangdese Batholith, Southern Tibet: Fractional Crystallization of Felsic Melts from Juvenile Lower Crust. (15th September 2021) - Zhang, Ying-Ze; Wang, Xiao-Lei; Li, Jun-Yong; He, Zhen-Yu; Zhang, Feng-Feng; Chen, Xin; Wang, Shuo; Du, De-Hong; Huang, Yu; Jiang, Chang-Hong
Abstract: The formation of high-silica leucogranites and related detailed evolution of granitic crystal mush in southern Tibet bear significant information on the tectonic and magmatic evolution of the Asian–Indian continent–continent collisional zone. Here, we first report an integrated investigation of the Oligocene (ca. 30 Ma) leucogranites and main body granitoids exposed within the Gangdese Batholith in Gyaca County, southern Tibet. The Gyaca leucogranites can be divided into two groups in terms of field observation (gradational contacts vs. dykes), petrography and geochemistry (plagioclase fractionation vs. accumulation trends), and are characterized by their formation through different stages of evolution from (early) fractionation to (later) accumulation (up to 30%) of plagioclase for Group I and II leucogranites, respectively. Overall, the two groups of leucogranites are both characterized by high SiO2 (71.4–75.7 wt.%), Na2 O/K2 O (>1.0) and Sr/Y (58–629), and low Rb/Sr (0.02–0.27). The Gyaca main body granitoids resemble the published Gangdese granitoids and most of them also have high Na2 O/K2 O and they generally show varied SiO2 (64.4–76.1 wt.%) and other major and trace elements. The Gyaca leucogranites and main body granitoids have very similar Sr–Nd–Hf–O isotopic compositions, with initial 87 Sr/ 86 Sr ratios from 0.7054 to 0.7064, ɛNd (t) values from −3.40 to +0.65, zircon ɛHf (t) values from −3.0 to +5.2, and zircon δ 18 O values from 5.59‰ to 6.84‰. These leucogranites and main body granitoids are interpreted to have a same magma source and can be formed by water-present melting of garnet amphibolites from juvenile lower crust plus minor materials from felsic ancient crust beneath the southern Lhasa Terrane. The genetic association of the Oligocene Gyaca leucogranites and main body granitoids and their geochemical diversity reveal an evolved magmatic system. The two types of leucogranites are probably formed by crystal-melt fractionation and plagioclase accumulation at different stages during the solidification of the magma chamber. The discovery of ca. 30 Ma leucogranites in the Gangdese Batholith, in combination with the Oligocene–Miocene high Sr/Y Gangdese granitoids and coeval Himalayan leucogranites (HLGs), indicate the coexistence of diverse granitic rocks in southern Tibet may principally result from partial melting of local deep crustal materials. A new petrogenetic model which illustrates the evolution and multiple emplacements of crystal mush in a granitic magma chamber is proposed for the formation and magmatic evolution of leucogranites in melts from juvenile lower crust in Tibet.